2021
DOI: 10.1016/j.burnso.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 in a newly established burn center

Abstract: Objective This study aims to investigate the effects of COVID-19 on epidemiological features, burn agent, burn percentage, and hospitalization time in a burn center. Methods This single-center, retrospective study included a total of 401 patients admitted to our study center between October 2019 and July 2020. The patients who were admitted before March 1, 2020, were considered the pre-March group, and those who were admitted after March 1, 2020, were considered the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…5 In addition, Dayı et al reported that burn injuries were most common in the 0 to 2 age group. 10 In these studies, as in our study, no effect of the COVID-19 pandemic was not found on the age distribution of burn patients. We think that the main reason for the difference in age groups is that there are burn centres in our city that treat both adult and paediatric patients, and these patients prefer the relevant centres.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…5 In addition, Dayı et al reported that burn injuries were most common in the 0 to 2 age group. 10 In these studies, as in our study, no effect of the COVID-19 pandemic was not found on the age distribution of burn patients. We think that the main reason for the difference in age groups is that there are burn centres in our city that treat both adult and paediatric patients, and these patients prefer the relevant centres.…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, in the study of Akkoç et al, the most burned patient group before and after COVID‐19 was found to be 1 to 5 years old group 5 . In addition, Dayı et al reported that burn injuries were most common in the 0 to 2 age group 10 . In these studies, as in our study, no effect of the COVID‐19 pandemic was not found on the age distribution of burn patients.…”
Section: Discussionsupporting
confidence: 49%
“…Although some burn units have reported their measures [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], there are no data on the impact of these with regard to treatment outcomes. Most of the data published in the literature thus far refer to epidemiological and demographic data in addition to injury and treatment characteristics of burn patients [ 8 , 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%